(untitled) (Applied Biological Research, 2016)
A field experiment was conducted in kharif 2012 and 2013 at MRCFC, SKUAST, Khudwani (Kashmir) on a silty clay loam soil to evaluate the impact of water regimes and weed management practices on nutrient uptake in rice and weeds under SRI. The soil at experimental site was neutral in reaction, medium in available P, K and organic carbon and low in available N. The treatments comprised of 3 irrigations schedules [alternate wetting and drying (AWD), continuous saturated condition and continuous flooding] and 7 weed management practices viz., 4 herbicidal treatments [pyrazosulfuron ethyl @ 20 g a.i. ha-1 (3 DAT); cyhalofop butyl @ 80 g a.i. ha-1 (15 DAT); pyrazosulfuron ethyl 20 g a.i. followed by cyhalofop butyl 80 g a.i. ha-1 (3 and 15 DAT), and butachlor @ 1.5 kg a.i. ha-1 (3 DAT)]; cono weeding, weedy check and weed-free control. The results revealed that saturated water regime treatment had highest uptake of macronutrients by grain and straw, while highest uptake of macro-nutrients by weeds was in AWD and lowest in continuous flooding. Among weed control measures, the lowest macronutrients uptake by crop was associated with post-emergence application of cyhalofop-butyl and highest amount of NPK depletion by weeds was observed in unweeded control. Minimum NPK uptake by weeds was noticed in sequential application of pyrazosulfuron-ethyl @ 20 g a.i. ha-1 and cyhalofop-butyl @ 60 g a.i. ha-1 treatment.